The evolution of business ethics research in the realm of tourism and hospitality: a bibliometric analysis. Issue 8 (8th August 2016) - Köseoğlu, Mehmet Ali; Sehitoglu, Yasin; Ross, Gary; Parnell, John
Abstract : Purpose: This paper illustrates how business ethics research is progressing in the tourism and hospitality industries, and suggests a research agenda. Design/methodology/approach: This study applies bibliometric analysis to articles related to business ethics topics in the tourism and hospitality fields published between 1995 and 2014 in six leading hospitality-oriented journals, nine leading tourism-oriented journals, and five leading business ethics-oriented journals. Findings: This study provides a broad view on business ethics research in the tourism and hospitality fields based on leading authors, institutions, themes, and methods employed over the last two decades. Research limitations/implications: This study assesses the progress of business ethics research in the hospitality and tourism fields. Only articles published in select, prominent SSCI journals were analyzed. Practical implications: This analysis focuses on published articles related to business ethics in the tourism and hospitality fields. As such, it facilitates researchers, academic scholars, and professionals in contributing to the field more effectively and advancing scientific progress in the literature. It aids practitioners by evaluating the extent to which scholars have investigated key issues in the field. Originality/value: This study is the first to utilize bibliometric analysis to assess business ethics research focusing on tourism and hospitality activities published in leading tourism, hospitality, and business ethics journals.